Evaluation of College Students' Innovation and Entrepreneurship Abilities in the New Media Environment Using Tree Soft Set and Neutrosophic Modeling - Xiang Lou (Neutrosophic Sets and Systems)
In today's rapidly evolving digital society, the new media environment has profoundly reshaped the landscape of innovation and entrepreneurship among college students. Understanding and evaluating students' abilities in this context are crucial for universities, policymakers, and industries seeking to cultivate future leaders and innovators. However, traditional evaluation frameworks often struggle to address the multi-layered, uncertain, and dynamic nature of competencies in a media-driven environment. This study proposes a novel decision-making framework based on Tree Soft Set (TSS) theory to evaluate college students' innovation and entrepreneurship abilities comprehensively. The TSS model, by organizing evaluation criteria into hierarchical tree structures, captures complex relationships among competencies and adapts flexibly to overlapping and uncertain information. To further enhance the robustness of the model, Single-Valued Neutrosophic Sets (SVNS) are integrated, enabling better representation of truth, indeterminacy, and falsity degrees in expert judgments. The proposed evaluation model identifies critical dimensions such as creativity, opportunity recognition, risk management, technological adaptability, communication skills, and leadership under the influence of new media. Criteria weighting is determined using the SWARA method, while final ranking of student profiles is achieved via the MAIRCA method. Empirical application and sensitivity analyses validate the framework’s stability and effectiveness. The results provide actionable insights for educational institutions aiming to nurture innovation-driven talent in the digital era.